Combined effects of physical activity, cognitive activity, and dietary patterns on cognitive impairment in older adults with consideration of APOE genotype: a cohort study - Wen-Fang Zhong; Xiao-Meng Wang; Huan Chen; Wei-Qi Song; Jian Gao; Pei-Liang Chen; Qiao-Qiao Shen; Fang-Fei You; Chuan Li; Yue-Bin Lv; Zhi-Hao Li; Xiao-Ming Shi; et al. (Alzheimer’s Research & Therapy)
Abstract Background This study aims to evaluate the combination effects of physical activity (PA), cognitive activity (CA), and dietary patterns impacts cognitive impairment among older adults, and whether these associations differ by apolipoprotein E (APOE) genotype. Methods A total of 18,909 adults aged 65 years or older at baseline were enrolled from 1998 to 2014 years. PA and CA was assessed using scores that reflected participation in various activities, and a total activity (TA) score was calculated as the sum of PA and CA scores. Diet quality was assessed with the SHE-index. Participants were categorized into lifestyle groups based on combinations of activity levels and SHE-index. The APOE genotype was categorized as APOEε4 carriers versus non-carriers. Cognitive function was evaluated using the Mini-Mental State Examination at baseline and follow-up. Adjusted Cox proportional hazards models was used to estimate the association and interaction between lifestyle and APOE genotype on the risk of cognitive impairment. Results During a mean follow-up time of 5.27 ± 3.67 years, 5713 participants developed cognitive impairment. Participants with higher levels of TA, PA, or CA, combined with a healthy diet, consistently exhibited the lowest risk of cognitive impairment, with hazard ratios (HR) of 0.65 [95% confidence intervals (CIs): 0.60–0.71] for TA, 0.72 (95% CI: 0.66–0.78) for PA, and 0.73 (95% CI: 0.67–0.79) for CA. This protective effect remained consistent across APOEε4 genotype groups, with HRs ranging from 0.54 to 0.67 in carriers and 0.63 to 0.69 in non-carriers for higher TA, PA, or CA combined with a healthy diet. In addition, participants engaging in high PA, high CA, and a healthy diet simultaneously showed the greatest protection against cognitive impairment, with HRs of 0.46 (95% CI: 0.28–0.76) in APOEε4 carriers and 0.47 (95% CI: 0.37–0.58) in non-carriers. Conclusions The greatest decrease in cognitive impairment was observed among older Chinese adults adhering to both high activity levels and healthy diet, The protective effect was even stronger when high physical activity, high cognitive activity, and a healthy diet were maintained simultaneously, and this trend was consistent regardless of APOEε4 status.